Type 2 Diabetes Self-Management Variables and Predictors. (September 2022) - Emery, Karin A.; Robins, Jo; Salyer, Jeanne; Thurby-Hay, Linda; Djira, Gemechis
Guided by the Self and Family-Management framework, relationships between diabetes distress, self-efficacy, resilience and outcomes of A1c, quality of life and health status were explored. A cross-sectional descriptive design was used. Seventy eight individuals were enrolled from US clinics. Data were analyzed to test for associations, main effects and interactions and predictors of self-management. Results indicated low diabetes distress ( M = 20.53), high self-efficacy ( M = 7.32), moderate resilience ( M = 80.27), and mean A1c 7.35%/56.88 mmol/mol. Seventy six percent of participants scored above the mental health norm, and 46% scored above the physical health norm. The average weighted quality of life score was −1.74. Diabetes distress was negatively associated with self-efficacy, resilience, physical health, mental health, and quality of life. Self-efficacy was positively associated with resilience, physical health, and quality of life. Resilience was positively associated with physical health, mental health and quality of life. Positive associations were found between quality of life, and physical and mental health. No associations were found between A1c and variables in the study. Multiple significant interactions were found with A1c, mental health and quality of life outcomes. Terms in the model included treatment regimen, years since diagnosis, provider collaboration, and history of diabetes self-management education. Distress was a significant predictor of health status and quality of life. The results confirm self-management facilitators self-efficacy and resilience and barrier diabetes distress and their relationships with outcomes in the framework. This study contributes to the understanding of the emotional aspect of diabetes. Continuing this work will allow researchers to better understand self-management, support self-management efforts and better outcomes.